ABT Based Load Frequency Control of Interconnected Power System. Issue 8 (8th May 2016) - Hasan, Naimul, Ibraheem; Ahmad, Samiuddin
Abstract: This article presents a frequency dependant price signal based new automatic generation control scheme for an interconnected power system. A two-area interconnected power system model consisting of four thermal generating stations in each area is considered under this work. All generators are operating with primary/conventional automatic generation control scheme or availability based tariff automatic based generation control scheme and each generator is owned by a separate generation company. The implementation of an availability based tariff based automatic generation control scheme is carried out for switching operations between automatic generation control and non-automatic generation control mode, which is based on the difference of the generator's marginal cost and real time frequency dependent price of unscheduled generation. The performance of generators employing primary/conventional automatic generation control scheme or availability based tariff based automatic generation control scheme has been investigated. A commercial case study is carried out to demonstrate effectiveness of the proposed control scheme.